Analysis and Determination of Self-Inductance through Direct and Indirect Measurements Methods - Herawati, Herawati; Khotimah, Siti Nurul; Munir, Muhammad Miftahul (JIPF (Jurnal Ilmu Pendidikan Fisika), 2024)
Practicum is an activity that helps students to understand an abstract concept. One of the concepts in physics that requires practicum is the concept of electricity. Inductance is an electrical quantity studied in high and vocational high schools. This study aims to determine the inductor's inductance value using several methods and analyze the most suitable method for determining the inductor inductance value. The inductor used is a commercial inductor with a color band code with an inductance value of 2.7 mH and a tolerance of 10%. Inductor inductance measurements were carried out using a benchtop LCR meter, handheld LCR meter, series RLC method, and LC resonance method. Each measuring instrument requires a frequency setting: refer to the manual for benchtop and handheld LCR meters, the resonant frequency for the serial RLC method, and adjusting the AFG (arbitrary function generator) frequency. Hence, a clear oscillation pattern is visible on the oscilloscope. The results of this study indicate that measurements using benchtop LCR meters, handheld LCR meters, and LC resonance methods produce inductance values within the inductance tolerance limits.